Nano-rod Ca-decorated sludge derived carbon for removal of phosphorus. (February 2018) - Kong, Lingjun; Han, Meina; Shih, Kaimin; Su, Minhua; Diao, Zenghui; Long, Jianyou; Chen, Diyun; Hou, Li'an; Peng, Yan
Abstract: Recovering phosphorus (P) from waste streams takes the unique advantage in simultaneously addressing the crisis of eutrophication and the shortage of P resource. A novel calcium decorated sludge carbon (Ca-SC) was developed from dyeing industry wastewater treatment sludge by decorating calcium (Ca) to effectively adsorb phosphorus from solution. The X-ray diffraction (XRD) and Fourier transform infrared (FTIR) techniques were used to characterize the Ca-SCs, followed by isotherm and kinetic sorption experiments. A preferred design with CaCO3 to sludge mass ratio of 1:2 was found to have a sorption capacity of 116.82 mg/g for phosphorus. This work reveals the crucial role of well-dispersed nano-rod calcium on the Ca-SC surface for the sorption of phosphorus. Moreover, the decoration of nano-rod calcium was found to further promote the uptake of phosphorus through the formation of hydroxylapatite (Ca5 (PO4 )3 (OH)). Thus, the development of decorated Ca-SC for sorption of phosphorus is very important in solving the P pollution and resource loss. Graphical abstract: Image 1 Highlights: Nano-rod Ca was dispersed on the SC surface. Sludge was converted into sorbent for P nutrient removal. Langmuir model fitted well with the isotherm sorption to P. Pseudo-second order model fitted well with the sorption kinetic to P. Crystallization of P and Ca contribute to the preferable removal mechanisms. Abstract : Well-dispersed nano-rod calcium decorated sludge carbon performs preferable ability to remove phosphorus.